2013
DOI: 10.1002/dev.21117
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of neonatal morphine administration on the pentylenetetrazol seizure model in rats: The role of hippocampal cholinergic receptors in adulthood

Abstract: Early life exposure to opiates may affect neuropathological conditions, such as epilepsy, during adulthood. We investigated whether neonatal morphine exposure affects pentylenetetrazol (PTZ)-induced seizures in adulthood. Male rats were subcutaneously injected with morphine or saline on postnatal days 8-14. During adulthood, each rat was assigned to 1 of the following 10 sub-groups: saline, nicotine (0.1, 0.5, or 1 μg), atropine (0.25 or 1 μg), oxotremorine M (0.1 or 1 μg), or mecamylamine (2 or 8 μg). An intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…On the other hand, there is a large body of evidence indicating diverse features of opioid agonists like morphine in seizure susceptibility in various models (kindling and PTZ‐induced) and phases (acute and chronic). Several studies have reported that low doses of morphine have an anticonvulsive impact in acute and chronic administrations, although high doses lower the seizure threshold . In line with previous studies, some paradoxical effects of opioid agonists were observed in our experiments.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, there is a large body of evidence indicating diverse features of opioid agonists like morphine in seizure susceptibility in various models (kindling and PTZ‐induced) and phases (acute and chronic). Several studies have reported that low doses of morphine have an anticonvulsive impact in acute and chronic administrations, although high doses lower the seizure threshold . In line with previous studies, some paradoxical effects of opioid agonists were observed in our experiments.…”
Section: Discussionsupporting
confidence: 91%
“…Controversially, the postnatal treatment of male rats with morphine reduced the development of pentylenetetrazol (PTZ)-induced seizures and the mortality rate in adulthood, possibly through the activation of GABAergic neurons in the hippocampus (Saboory et al, 2014). This effect was very similar to the consequences of prenatal morphine treatment, with decreased susceptibility to GABA-regulated seizures (Vathy, 2001).…”
Section: Experimental Conditions In Rodentsmentioning
confidence: 97%
“…In a model of morphine sensitization in rats, autoradiography revealed a significant increase in the number of MORs in the hippocampus (Vigano et al, 2003) that making this system one of the predominant endogenous modulatory mechanisms that affect seizure susceptibility. Although the hippocampal formation is a structure that expresses significant densities of opioid receptors, morphine and other neurotransmitters including glutamate, acetylcholine, GABA, and nitric oxide appear to have a functional relationships (Saboory et al, 2014). The co‐localization between hippocampal MOR and GABAergic interneurons is observed in CA1, CA3, and dentate gyrus regions in rats, suggesting that these receptors can directly control hippocampal GABAergic neuronal activity (Kalyuzhny and Wessendorf, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Opioids appear to have a complex influence on neuronal excitability. The pro‐ or anti‐convulsant activity of an opioid compound depends not only on its affinity to specific opioid receptor, but also on the dose, route of administration, and animal model (Saboory et al, 2007; Saboory et al, 2014). Generally, opioids tend to inhibit neuronal activity.…”
Section: Introductionmentioning
confidence: 99%